2022
DOI: 10.1007/s00126-022-01141-z
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Pt/Pd ratios in Bushveld magmas and cumulates: a review complemented by new W isotope data

Abstract: The Bushveld Complex of South Africa is underlain by a fine-grained sill complex which most workers interpret to represent the quenched parent magmas to the intrusion. The sills have unusually high Pt contents (up to ~ 25 ppb) and Pt/Pd ratios (average 1.50) exceeding those in most other mantle magmas globally. Unusually high Pt/Pd is also found in many Bushveld cumulates. Understanding the origin of the high Pt/Pd is important for exploration, in view of the contrasting monetary value of the metals, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Park et al (2013) found a decrease in Pd/Pt ratios of Pual Ridge lavas and they suggested that sulfide melt segregation would cause Pd/Pt ratio to drop due to higher sulfide-silicate partition coefficient (D) Pd has than Pt. In addition, Maier et al (2022) also proposed that the variation in 𝐷 𝑃𝐺𝐸𝑠 𝑠𝑢𝑙𝑓𝑖𝑑𝑒 𝑚𝑒𝑙𝑡−𝑠𝑖𝑙𝑖𝑐𝑎𝑡𝑒 𝑚𝑒𝑙𝑡 might be responsible for the anomalous Pd/Pt ratio found at the Bushveld Complex, while also alluding to the possible presence of a Pt-rich primordial mantle domain. While there is a long-standing debate on the partition coefficients of PGEs, the experiments performed by Mungall and Brenan (2014) suggested that 𝐷 𝑃𝑡 and 𝐷 𝑃𝑑 are almost identical with no clear evidence such that one is consistently higher than the other; those authors proposed that low Pd/Pt in the Bushveld resulted from partial melting of a source mantle rich in residual Pt alloy but lacking in sulfide-hosted Pd.…”
Section: Other Possible Mechanisms For the Decoupling Of Pd And Pt In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al (2013) found a decrease in Pd/Pt ratios of Pual Ridge lavas and they suggested that sulfide melt segregation would cause Pd/Pt ratio to drop due to higher sulfide-silicate partition coefficient (D) Pd has than Pt. In addition, Maier et al (2022) also proposed that the variation in 𝐷 𝑃𝐺𝐸𝑠 𝑠𝑢𝑙𝑓𝑖𝑑𝑒 𝑚𝑒𝑙𝑡−𝑠𝑖𝑙𝑖𝑐𝑎𝑡𝑒 𝑚𝑒𝑙𝑡 might be responsible for the anomalous Pd/Pt ratio found at the Bushveld Complex, while also alluding to the possible presence of a Pt-rich primordial mantle domain. While there is a long-standing debate on the partition coefficients of PGEs, the experiments performed by Mungall and Brenan (2014) suggested that 𝐷 𝑃𝑡 and 𝐷 𝑃𝑑 are almost identical with no clear evidence such that one is consistently higher than the other; those authors proposed that low Pd/Pt in the Bushveld resulted from partial melting of a source mantle rich in residual Pt alloy but lacking in sulfide-hosted Pd.…”
Section: Other Possible Mechanisms For the Decoupling Of Pd And Pt In...mentioning
confidence: 99%
“…While there is a long-standing debate on the partition coefficients of PGEs, the experiments performed by Mungall and Brenan (2014) suggested that 𝐷 𝑃𝑡 and 𝐷 𝑃𝑑 are almost identical with no clear evidence such that one is consistently higher than the other; those authors proposed that low Pd/Pt in the Bushveld resulted from partial melting of a source mantle rich in residual Pt alloy but lacking in sulfide-hosted Pd. Besides, for systems with relatively low R-factor such as the massive sulfide accumulations at Raglan (300-1000) and the basal mineralization in Flatreef (~1000), the PGE contents are insensitive to the potential difference in D (Maier et al, 2022). Taking Raglan as an example, the Pd/Pt ratio of 3 cannot be reproduced by manipulating model partition coefficients without assuming unrealistically low 𝐷 𝑃𝑡 (~500) which is more than three orders of magnitude smaller than assumed 𝐷 𝑃𝑑 .…”
Section: Other Possible Mechanisms For the Decoupling Of Pd And Pt In...mentioning
confidence: 99%